2001
DOI: 10.1007/s001340101039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the prognosis of multiple, severely traumatized children in the intensive care unit

Abstract: PRISM is a reliable tool for evaluating the prognosis of multiple, severely traumatized children. Its relative simplicity and the fact that it is extremely widespread as a general prognosis score in PICUs represent other arguments for its use. Due to the leading influence of head trauma on mortality, GCS, a score even simpler than PRISM, showed identical accuracy regarding survival prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 0 publications
3
44
2
3
Order By: Relevance
“…17,18 However, its accuracy for the prediction of mortality is still debated. [19][20][21] In our study, the mortality rate was very low (1.8%), and all deaths occurred in patients in the STG (PTS ≤8). Their PTS scores were four or lower.…”
Section: Discussionmentioning
confidence: 56%
“…17,18 However, its accuracy for the prediction of mortality is still debated. [19][20][21] In our study, the mortality rate was very low (1.8%), and all deaths occurred in patients in the STG (PTS ≤8). Their PTS scores were four or lower.…”
Section: Discussionmentioning
confidence: 56%
“…In a similar study including children with severe trauma in intensive care, Cantais et al reported that the same systems had significant association with mortality, though the GCS had the highest predictive ability. [21] Furthermore, in a study in which 11 trauma parameters were compared among children and adults, Otto et al reported that physical parameters, including the GCS, had higher predictive ability than those that were anatomical, including the PTS and ISS. [22] …”
Section: Discussionmentioning
confidence: 99%
“…28 Its use has been reported in children with TBI, 9,12 and PTS < 3 is associated with an increased rate of mortality. 3,12 Although widely used in the assessment of pediatric trauma patients, in this study the PTS failed to correlate with any of the physiological variables known to be associated with secondary insults.…”
Section: Pediatric Trauma Scorementioning
confidence: 56%
“…3,6,9,16 Given that sedation in the acute phase may influence 2 components of the GCS, (eye opening and verbal responses), the motor component of the GCS is often considered to represent a more reliable assessment. For preverbal children, the pediatric coma scale is preferred.…”
Section: Glasgow Coma Scalementioning
confidence: 99%